2023
DOI: 10.1101/2023.09.18.558209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling of 12 chromosomal inversions maintains a strong barrier to gene flow between ecotypes

Alan Le Moan,
Sean Stankowski,
Marina Rafajlovic
et al.

Abstract: Chromosomal rearrangements lead to the coupling of reproductive barriers, but whether and how they contribute to completion of speciation remains unclear. Marine snails of the genusLittorinarepeatedly form hybrid zones between taxa segregating for inversion arrangements, providing opportunities to study this question. Here, we analysed two adjacent transects across hybrid zones between large and dwarf ecotypes ofLittorina fabaliscovering wave exposure gradients in a Swedish island. Applying whole-genome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In spite of mounting support for inversions having a role in speciation (Jones et al, 2012;Küpper et al, 2016;Tuttle et al, 2016;Hooper and Price, 2017;Wellenreuther and Bernatchez, 2018;Faria, Chaube, et al, 2019;Faria, Johannesson, et al, 2019;Lucek et al, 2023), studies that uncover how they contribute to coupling of genes underlying ecological and reproductively isolating traits, enabling the formation of persistent species are scarce (but see Meyer et al, 2023;Moan et al, 2023). We find compelling evidence for a large inversion enabling host race specific adaptation and progress towards speciation in T. conura.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of mounting support for inversions having a role in speciation (Jones et al, 2012;Küpper et al, 2016;Tuttle et al, 2016;Hooper and Price, 2017;Wellenreuther and Bernatchez, 2018;Faria, Chaube, et al, 2019;Faria, Johannesson, et al, 2019;Lucek et al, 2023), studies that uncover how they contribute to coupling of genes underlying ecological and reproductively isolating traits, enabling the formation of persistent species are scarce (but see Meyer et al, 2023;Moan et al, 2023). We find compelling evidence for a large inversion enabling host race specific adaptation and progress towards speciation in T. conura.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several genomic inversions showing allelic frequency differences between ecotypes (Faria et al 2019a; Westram et al 2021), sex association (Hearn et al 2022) and association with adaptive traits (Koch et al 2021; 2022) have been identified in L. saxatilis and other species of the genus (Reeve et al 2023; Le Moan et al 2023). Inversions can promote the process of local adaptation and speciation and are associated with ecotype divergence in several other natural systems, e .…”
Section: Introductionmentioning
confidence: 99%
“…saxatilis and other species of the genus (Reeve et al 2023;Le Moan et al 2023). Inversions can promote the process of local adaptation and speciation and are associated with ecotype divergence in several other natural systems, e.g.…”
Section: Introductionmentioning
confidence: 99%